2015
DOI: 10.1542/peds.2014-1822
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Measles-Containing Vaccines in 1-Year-Old Children

Abstract: BACKGROUND AND OBJECTIVES: All measles-containing vaccines are associated with several types of adverse events, including seizure, fever, and immune thrombocytopenia purpura (ITP). Because the measles-mumps-rubellavaricella (MMRV) vaccine compared with the separate measles-mumps-rubella (MMR) and varicella (MMR + V) vaccine increases a toddler's risk for febrile seizures, we investigated whether MMRV is riskier than MMR + V and whether either vaccine elevates the risk for additional safety outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 40 publications
2
24
1
1
Order By: Relevance
“…Clustering of febrile seizures in the 2 weeks following MMR containing vaccines is an expected finding, given previous studies which demonstrate an association, with the greatest risk occurring between day 5 and day 12 following vaccination [10,[13][14][15][16]. It is not possible to determine causality in this study though, especially given that half of the subjects with febrile seizure following MMR also had at least one virus identified.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Clustering of febrile seizures in the 2 weeks following MMR containing vaccines is an expected finding, given previous studies which demonstrate an association, with the greatest risk occurring between day 5 and day 12 following vaccination [10,[13][14][15][16]. It is not possible to determine causality in this study though, especially given that half of the subjects with febrile seizure following MMR also had at least one virus identified.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have suggested a possible role for Influenza, Adenovirus and Human Herpesvirus 6 (HHV6) [4][5][6][7][8][9]. Recent literature has focused on the possible association between febrile seizures and complications of vaccine administration, with particular emphasis on Measles-containing vaccines [10][11][12][13][14][15][16]. In Australia in 2010 there was an increase of reported incidence of children with febrile adverse events following administration of one brand of trivalent influenza vaccine (bioCSL FluVax®).…”
Section: Introductionmentioning
confidence: 99%
“…More serious adverse effects include seizures, which are more frequent in children with a personal or family history of febrile seizures and family history of epilepsy. Among 12– to 23‐month‐olds, vaccination with MMR and varicella leads to 1 seizure per 2300 doses, with this rate doubling for those children receiving the combined MMRV vaccine . Therefore, the MMRV vaccine is only recommended to be given as the 4– to 5‐year dose and not at 12–15 months.…”
Section: Safety Of Mmr Vaccinementioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) in the U.S. recommended 26 vaccine doses for infants in 2007 with clinical implications suggesting deleterious impacts on infants' health due to uncharacterized interference among unrelated vaccines after consecutive cycles of intensive immunization [8]. All measlescontaining vaccines are associated with several types of adverse events, including seizure, fever, and immune thrombocytopenia purpura [9]. this invasive mode invariably induces a systemic burst of overly exuberant inflammation in nearly all vaccinees shortly post-injection.…”
mentioning
confidence: 99%